Temporal trends in femoral diaphyseal torsional asymmetry among the Arikara associated with postural behavior. Issue 4 (24th May 2014) - Wescott, Daniel J.; Cunningham, Deborah L.; Hunt, David R.
ABSTRACT Average femoral torsion has been reported to differ among populations, and several studies have observed a relatively high prevalence of femoral anteversion asymmetry in Native Americans, especially females. This study investigates sexual dimorphism and temporal trends in femoral torsional asymmetry among the Arikara from the seventeenth to the early nineteenth century. To establish if there are population differences, femoral torsion was first measured using a direct method on a diverse comparative sample of Native Americans from the Southwest, Midwest, and Great Plains as well as American Whites and Blacks. To examine temporal trends among the Arikara, femoral torsion was examined using the orientation of the maximum bending rigidity at subtrochanteric in 154 females and 164 males from three temporal variants of the Arikara Coalescent tradition. There is significant sexual dimorphism in femoral torsional directional and absolute asymmetry among most Native American samples, but not among American Whites and Blacks. Among the Arikara there is significant sexual dimorphism in femoral torsional asymmetry in all three temporal variants, and asymmetry in femoral torsional asymmetry increased significantly from the protohistoric to the early historic period among females. The increased femoral torsional asymmetry is likely associated with a common side‐sitting posture observed in historic photographs of Great Plains females. Historic Arikara females may have habitually sat in this compulsory position for extended periods while conducting domestic chores. The dramatic change from the protohistoric to historic period suggests a cultural change in sitting posture among females that was widespread across the Northern Plains. Am J Phys Anthropol 154:512–524, 2014. © 2014 Wiley Periodicals, Inc.